EXPLORING THE RELATIONSHIP BETWEEN CLASSROOM CLIMATE, ACADEMIC SATISFACTION, AND LIFE SATISFACTION OF UNIVERSITY STUDENTS - Ahmed, Yusra; Yousuf, Tahira; Shoaib , Sidra; Nawaz , Binish; Ali, Syed Kawish; Maheshwary, Neeta; Ahmed, Arjumand (Journal of Pakistan Psychiatric Society, 2025)
OBJECTIVETo assess the relationships between the classroom climate, academic satisfaction, and life satisfaction of university students in Pakistan. STUDY DESIGNCross-sectional studyPLACE AND DURATION OF STUDYThe study was conducted at the Institute of Professional Psychology at Bahria University Karachi, Pakistan, from May to October 2022.METHODA sample of 271 university students, aged 18 to 45 were approached via convenience sampling. The College and University Classroom Environment Inventory was administered to measure the classroom climate while the Satisfaction with Life Scale was utilized to evaluate academic and life satisfaction.RESULTSThe study found a significant positive correlation between Classroom Climate (CC) and both Academic Satisfaction (r = .26, p < .01) and Life Satisfaction (r = .18, p < .01). Regression analysis showed that CC explained 35% of the variance in Academic Satisfaction (R² = .35, p < .001) and 32% in Life Satisfaction (R² = .32, p < .001). Graduate students reported higher academic satisfaction and better classroom climate perception than undergraduates (F = 10.95, p < .05), while doctoral students exhibited lower satisfaction levels.CONCLUSIONThe findings show how crucial the classroom climate is in influencing students' academic satisfaction and life satisfaction. An encouraging and dynamic classroom climate promotes better learning experiences and wellbeing.